2013
DOI: 10.1017/jfm.2013.114
|View full text |Cite
|
Sign up to set email alerts
|

Worst-case amplification of disturbances in inertialess Couette flow of viscoelastic fluids

Abstract: Amplification of deterministic disturbances in inertialess shear-driven channel flows of viscoelastic fluids is examined by analyzing the frequency responses from spatio-temporal body forces to the velocity and polymer stress fluctuations. In strongly elastic flows, we show that disturbances with large streamwise length scales may be significantly amplified even in the absence of inertia. For fluctuations without streamwise variations, we derive explicit analytical expressions for the dependence of the worst-c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 31 publications
2
32
1
Order By: Relevance
“…An important question is whether the streamwise vortex would be observed in practice in a real flow. Previous linear analyses of the flow response to body forces in both Newtonian (Bamieh & Dahleh 2001;Jovanović & Bamieh 2005) and weakinertia viscoelastic (Lieu et al 2013) flows highlight a flow sensitivity to streamwise elongated disturbances with O(1) spanwise spacing. This sensitivity underscores the importance of the current results.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An important question is whether the streamwise vortex would be observed in practice in a real flow. Previous linear analyses of the flow response to body forces in both Newtonian (Bamieh & Dahleh 2001;Jovanović & Bamieh 2005) and weakinertia viscoelastic (Lieu et al 2013) flows highlight a flow sensitivity to streamwise elongated disturbances with O(1) spanwise spacing. This sensitivity underscores the importance of the current results.…”
Section: Resultsmentioning
confidence: 99%
“…Their analysis provides further evidence of similarities between polymer stretching in highly elastic flows and tilting of mean vorticity in high-Reynolds-number Newtonian flows. Recently, these results have been extended to a more realistic polymer model, where the large energy growth generated by polymer stretch is upper bounded by the maximum extensibility of the polymer chains (Lieu et al 2013). …”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Equally, there is the possibility of non-modal growth [13][14][15]. Essentially, if the linear stability problem has close eigenvalues, we may see transient growth of disturbances even if the long-time behaviour (predicted by the sign of the eigenvalues) is stable.…”
Section: Other Possible Mechanismsmentioning
confidence: 99%
“…The flow response takes the form of streamwise streaks, similar in appearance to inertial transient growth in Newtonian fluids. Further studies have addressed the influence of weak inertia (Page & Zaki 2014) and finite polymer extensibility (Lieu, Jovanović & Kumar 2013) on this elastic growth. In inertia-dominated flows, Hoda, Jovanović & Kumar (2008, 2009 introduced stochastic forcing in the linear equations for an Oldroyd-B fluid and demonstrated that viscoelasticity enhances the energy density of the response.…”
Section: Disturbance Amplification In Viscoelastic Flowsmentioning
confidence: 99%